Rare Primary Paraovarian Adenocarcinoma in Postmenopausal Woman: Case Report and Review (Global Journal of Medical Research, 2019)
Malignant paratubal cancers have extremely rare occurrence and have not been sufficiently described and discussed in literature. We describe case of an 80 years old gravida 5 para 4 postmenopausal woman presented with pain in lower abdomen and spotting per vagina. USG followed by MRI showed large mid pelvic right adnexal complex predominantly cystic lesion of 8.7×7.1×5.9 cm size with small exophytic solid component (3.1×2.8×2.6 cm). Postoperatively it was diagnosed as a case of high grade paratubal adenocarcinoma (stage T1N0M0). The patient received 3 cycles of adjuvant chemotherapy with carboplatin and docetaxel. Patient has had no recurrence till date (20 months post treatment).
Keywords: Paratubal adenocarcinoma; adnexal complex; primary tumour; broad ligament